2011
DOI: 10.3892/ijo.2011.1247
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CXCL10 as a novel serum marker for predicting liver metastasis and prognosis in colorectal cancer

Abstract: Abstract. The aim of this study was to identify novel and reliable serum markers related to the prognosis of colorectal cancer (CRC) patients and to assess the association between selected markers and clinical outcome. We performed experiments using cytokine arrays to investigate the cytokine profiles in serum from stage IV CRC patients, compared with those of stage I patients. Serum CXCL10 was measured using an ELISA in 218 CRC patients and 17 normal volunteers to clarify the association of CXCL10 with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 35 publications
4
45
2
Order By: Relevance
“…IP-10 featured in all disease comparison panels for diagnosis, consisitent with a previous small study in PDAC [32] and a study in colorectal cancer [33]. Increased expression of IP-10 and its receptor CXCR3 have also been associated with several advanced human cancers, including ovarian cancer, malignant melanoma, mutliple myeloma and basal cell carcinoma [34].…”
Section: Discussionmentioning
confidence: 61%
“…IP-10 featured in all disease comparison panels for diagnosis, consisitent with a previous small study in PDAC [32] and a study in colorectal cancer [33]. Increased expression of IP-10 and its receptor CXCR3 have also been associated with several advanced human cancers, including ovarian cancer, malignant melanoma, mutliple myeloma and basal cell carcinoma [34].…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies reported tumour-promoting as well as antimalignant functions of CXCL10 (5,1214,19). However, the expression profile of CXCL10 in CRC patients has not been fully evaluated.…”
Section: Discussionmentioning
confidence: 90%
“…This is not surprising because our sample size is relatively small and accumulating evidence has shown complex effects of cytokines in the tumor microenvironment, ranging from support to inhibition of tumor growth (23,45). IL1 and TNFα can be highly inflammatory in the tumor microenvironment and facilitate tumor growth, angiogenesis, and metastasis (27).…”
Section: Discussionmentioning
confidence: 93%